Positioning Control Of A One Mass Rotary System With CM NCTF Controller - Foo, Jia En; Chong, Shin Horng; Mohd Nor, Rozilawati; Loh, Ser Lee (Penerbit Universiti, UTeM, 2016)
In this paper, a Continuous Motion Nominal Characteristic Trajectory Following (CM-NCTF) controller is proposed as a practical control approach on a DC driven one mass rotary system. A CM-NCTF controller has simple controller structure and easy design procedures, and it does not require the exact plant model parameters. The CM-NCTF controller is made up of two major parts: a Nominal Characteristic Trajectory (NCT) and a Proportional-Integral (PI) compensator. The NCT is constructed on a phase plane with open loop information of the mechanism, while PI compensator is designed to ensure the mechanism follows the NCT and stops at the origin of the phase plane. The positioning performance of the CM-NCTF controller are evaluated and compared with a PID controller in point-to-point and tracking motion experimentally. The proposed controller achieved at least 36.8 % smaller steady state error than the PID controller, with no presence of overshoot in point-to-point motion. In tracking motion, the maximum tracking error produced by the CM-NCTF controller is 3 times lower than the PID controller in 1 rad amplitude. Overall, the experimental results demonstrated that the CM-NCTF controller has greater positioning and tracking performances than the PID controller.